TGH. ABDUL KARIMS DAKWAH AND MOVEMENTS FOR LOMBOK COMMUNITY DEVELOPMENT - adi fadli (Ulumuna, 2018)
Abstract: Pesantren - as stated by Gus Dur – is as a subculture not only has be been but become result of its founder concoction as of a form of contributed for society. In such of Pondok Pesantren Nurul Hakim Kediri West Lombok case which founded by TGH. Abdul Karim. Therefore, this paper tries to describe TGH. Abdul Karim contributions for Sasak Lombok society development by exploring his biography, regulation, and whatever in connection with it. This study more based on the results of interviews with primary sources, such as his friends, his students, and his family. This paper concludes that TGH. Abdul Karim is the founder of Pesantren Nurul Hakim Kediri Kediri West Lombok West Nusa Tenggara Islamic Boarding House. He was born on Tuesday, June 30, 1903 and died on Monday, May 10, 1976. He had been educated in Lombok and continued to Mecca and Medina. TGH. Abdul Karim  dakwah and movements was starting from the room of his own house (Kerbung). From kerbung to pondok pesantren or Public Islamic Boarding House. His Commitment in guiding and fostering the community was made him as a figure which always remembered by the community. The greatness of his name and the existence of Nurul Hakim Islamic Boarding House has been being a proof of his contribution for developing of the Sasak people in particular and community in general.